(untitled) (Biological Sciences - PJSIR, 2001)
Rheological andbaking tests werecarriedouton wheat-cocoyamcompositeflourmixedin different proportions. The results of the farinograms and extensograms showed that replacemtnt of wheat flour up to 20% level gave bread of acceptablequality.The proportionofextensibilityandresistancetoforcedecreasedwiththeincreaseofcocoyam flour in the composite mix. Mixing tolerance index also indicated the poor quality of the composite flour beyond 20% replacement. Breadmaking properties, as indicated by internal and external scores, also showed that beyond 20% replacement levelthebread wasunattractive andlacking in therequiredquality attributes.